Thermoresponsive polymer coated gold nanoparticles: from MADIX/RAFT copolymerization of N-vinylpyrrolidone and N-vinylcaprolactam to salt and temperature induced nanoparticle aggregation1. Issue 53 (11th June 2015) - Maji, Samarendra; Zhang, Zhiyue; Voorhaar, Lenny; Pieters, Sophie; Stubbe, Birgit; Van Vlierberghe, Sandra; Dubruel, Peter; De Geest, Bruno G.; Hoogenboom, Richard
<x xml:space="preserve">Abstract</x> In the present contribution, we report the synthesis of thermoresponsive homo and statistical copolymers of N-vinylcaprolactam and N-vinylpyrrolidone and the corresponding responsive gold nanoparticles.